Kinetics of fatigue crack growth and crack paths in the old puddled steel after 100-years operating time (Fracture and Structural Integrity, 2015)
The goal of the authors’ investigations was determination of the fatigue crack growth in fragmentsof steel structures (of the puddled steel) and its cyclic behavior. Tested steel elements coming from the turn ofthe 19th and 20th were gained from still operating ancient steel construction (a main hall of Railway Station,bridges etc.). This work is a part of investigations devoted to the phenomenon of microstructural degradationand its potential influence on their strength properties. The analysis of the obtained results indicated that thoselong operating steels subject to microstructure degradation processes consisting mainly in precipitation ofcarbides and nitrides inside ferrite grains, precipitation of carbides at ferrite grain boundaries and degenerationof pearlite areas [1, 2]. It is worth noticing that resistance of the puddled steel to fatigue crack propagation inthe normalized state was higher. The authors proposed the new kinetic equation of fatigue crack growth rate insuch a steel. Thus the relationship between the kinetics of degradation processes and the fatigue crack growthrate also have been shown. It is also confirmed by the materials research of the viaduct from 1885, which hasnot shown any significant changes in microstructure. The non-classical kinetic fatigue fracture diagrams (KFFD)based on deformation (??) or energy (?W) approach was also considered. In conjunction with the results oflow- and high-cycle fatigue and gradual loss of ductility as a consequence (due to the microstructuraldegradation processes) - it seems to be a promising construction of the new kinetics fatigue fracture diagramswith the energy approach.
Keywords: Puddled steel